Stability and power resistance of a multi-hull tourism boat / Badrul Amin Badrul Hisham, Shaharudin Ahmad, Amir Radzi Ab. Ghani - Badrul Hisham, Badrul Amin; Ahmad Shaharudin; Ab. Ghani, Amir Radzi (Smart Manufacturing Research Institute (SMRI), 2022)
This study is to analyse the stability and the power resistance of a multihull tourism boat. Tourism boats have a design that can accommodate a number of passenger and cargo, and travel at a desired speed. A multihull type boat can improve the intended stability characteristic for the safety of the passengers and also the powering of the boat for economic considerations. This study was conducted using a 12-meter catamaran hull form with three different loading conditions, (i) boat only displacement, (ii) boat with half capacity passengers and (iii) boat with full capacity passengers. This study aims to find the total resistance value of the boat to obtain the power needed for the boat to move at certain speed that is suitable for tourism. The hull form will also be analysed for its stability with the three different loading conditions. The result shows that the boat at 12 knots has a resistance of 21.04 kN needing more than 130 kW to operate at the given speed with the usable maximum resistance of 29.44 kN at speeds of 15 knots. The stability of the boat while operating was evaluated by comparing the results obtain with International Maritime Organization (IMO) criteria in MSC.36(63). Based on the analysis, it was concluded that the maximum GZ that the boat can handle is 1.58 m at an angle of 25 degree with full loading parameter and has met all the established standard.